Effect of short-term protein supplemention on ovulation rate and live weight of goats - Mohammed, Nur Hafizah; Ab Ghani, Nurul Izza; Yong, Christina Seok Yien; Shikh Maidin, Mashitah (UB Press, 2016)
Seventeen of matured female crossed-Boer goats with aged 2 to 3 years old were used to determine the effects of high protein intake on ovulation rate and live body weight. The does were divided into two groups; 1) Control group received maintenance diet (commercial pallet and napier grass) and 2) Treatment Group received double maintenance diet (commercial pallet-2M and napier grass). The feeding treatment was started 10 days prior to CIDR removal (Day 0) and last for 21 days. All the does were weighed every two weeks throughout the experiment. All does were synchronized with CIDR for 18 days (Day -18 to Day 0). On Day 16, ovaries were examined by ultrasound and ovulation rate were calculated by presence number of corpus luteum. Results showed that does supplemented with high protein intakes does not affects their live weight and ovulation rate (P>0.05). Therefore, we concluded that protein supplement on goat, does not give robust effect on the ovulation rate and live body weight.